Expression of ESR1, PRLR, GHR, and IGF1R in mammary glands of Hu sheep with four teats - Zhang, Lei; Peng, Fang; Yu, Fangbai; Wan, Lu; Zhou, Zhan-Qin (Czech Journal of Animal Science, 2019)
Supernumerary teats are commonly found in sheep. To investigate the expression levels of hormone receptors in supernumerary teats of Hu sheep, mammary tissue samples were collected from two groups of Hu sheep, four- and two-teat sheep, during adolescent (A), pregnancy (P), lactation (L), and non-pregnancy (N). Using hematoxylin and eosin staining, we found that mammary alveoli were denser in the four-teat sheep than in the two-teat sheep during P and L. Immunohistochemistry and Western blotting were used to detect the expression patterns and relative protein expression levels of the estrogen receptor 1 (ESR1), prolactin receptor (PRLR), growth hormone receptor (GHR), and insulin-like growth factor 1 receptor (IGF1R) in Hu sheep mammary glands during the four periods. All four receptors were mainly expressed in mammary epithelial cells and adipose cells. Furthermore, the expression levels of PRLR and GHR in the four-teat sheep were significantly higher than those in the two-teat sheep during P and L. Our data suggest that four-teat sheep have more developed mammary gland tissue compared with two-teat sheep.
Keywords: supernumerary teats; mammary tissue; immunohistochemistry; hormone receptor